AKSELERASI PEMAHAMAN MATERI SHARAF MELALUI METODE TAMYIZ BERBASIS PERAGAAN PADA MAHASISWA IAIN KENDARI - Wa Muna (Institut Agama Islam Negeri Kendari, 2017)
This research discusses the application the Tamyiz method based demonstration in learning Arabic as a measure to accelerate the understanding the content ofsharf through tamyiz methods for the students of second semester of Arabic Education Program (PBA) Tarbiyah Faculty and Science Teaching (FTIK) Inistitut Islamic Studies (IAIN) Kendari. This research is the Classroom Action Research (CAR), which is conducted within two cycles and three actions. The first cycle consists of four steps, are: Planning, action or measurement, Observation, Reflections.The results indicated that the application of Tamyiz methods based demonstration to accelerate the understanding content of sharf for the students of the second semester of PBA FTIK IAIN Kendari. From the total 20 students in pre-cycle it obtained that the total score 1257, and the average score of students is 62.85, the highest score is 85 and the lowest one is 50. There are two students who complete the minimum mastery score (KKM) 75. At the first cycle, the total score takes up 1476.88 with the highest score is 89 and the lowest one is 61.5 to obtain the average score 73.844 which represented an increase about 10.827, and nine people or 45% obtain the competence standard score. Meanwhile, the second cycle gain the total of score up to 1670 with the average score is 83.5 and the highest score is 100, and also the lowest one is 70. In this cycle, there are seven students or 85% who pass the passing grade.